Thomas Middleton, Renaissance dramatist - O'Callaghan, Michelle (Renaissance dramatists (Edinburgh, Scotland), 2009)
Thomas Middleton is one of the major English Renaissance dramatists alongside Marlowe, Shakespeare and Jonson. Middleton continues to fascinate audiences and readers with his black humour, his wry and witty treatment of sexuality, morality, and politics. He is a consummate professional dramatist, experimenting with stagecraft in a manner that combines the visual and the verbal to startling effect. This book brings together these aspects of Middleton's craft through a detailed study of his major plays. Middleton experimented with, and helped to shape, a range of dramatic genres: city comedy, tragicomedy, romance, and revenge tragedy. This new guide analyses in detail how the plays work in terms of the early modern theatre and dramatic genres, as well as elucidating the broader cultural issues shaping the plays. It provides an introduction to critical readings of Middleton's works as well as modern performances, demonstrating how modern critics, producers, dramatists and film makers see Middleton's dark, playful and challenging plays as speaking to our times. Key Features Ideal student guide with its wide ranging introduction to Middleton's city comedies, tragedies, and collaborative plays and its readings of key texts such as The Roaring Girl, Chaste Maid in Cheapside, Revenger's Tragedy, Women Beware Women, and The Changeling Uses the most recent edition available, the Oxford Middleton (2007) Provides background contexts guiding readers through criticism of the plays as well as recent work on early modern theatre and culture Emphasis on Middleton's stagecraft and its assessment of modern adaptations and film versions of his plays